Simulation of combustion characteristics in a hydrogen fuelled lean single-element direct injection combustor. (2nd February 2017) - Li, Jianzhong; Yuan, Li; Mongia, Hukam C.
Abstract: Combustion characteristics in a hydrogen fuelled single-element lean direct injection (LDI) combustor for low emission gas turbine engine are computationally investigated. A single-element LDI combustor was produced and simulated with steady-state Reynolds-averaged Navier–Stokes reacting computations. Reacting computations of the single-element LDI combustor were performed with an augmented reduced 23-step reaction mechanism for hydrogen/air. A realizable k  −  ε model was used to obtain turbulence closure. For the single-element LDI combustor with different equivalence ratio, the effective area, axial velocity, total pressure drop coefficient, total temperature, mass fraction of OH, emission index of pollutant NO (EINO ) were achieved and discussed. Highlights: Combustion characteristics in a hydrogen fuelled single-element lean direct injection (LDI) combustor are computationally investigated. Reacting computations of single-element LDI combustor were performed with an augmented reduced 23-step reaction mechanism for hydrogen/air. Effective area, velocity, pressure drop, temperature, mass fraction of OH, EINO and lean blowout of LDI with equivalence ratio were discussed.